PRINCIPAL'S LEADERSHIP MANAGEMENT IN IMPROVING THE QUALITY OF PERFORMANCE OF EDUCATORS AND EDUCATION PERSONNEL IN MADRASAH ALIYAH SUNGGAL - Basri, Hasan; Tambunan, Nurhalima (Proceeding International Seminar of Islamic Studies, 2023)
The purpose of this study is to determine the leadership management of school principals in improving the quality of performance of educators and education personnel in Madrasah Aliyah Sunggal. Improving the quality of performance of educators and education personnel has a significant impact on the educational process and the achievement of the desired educational goals. This paper uses a qualitative descriptive approach that seeks to explain the form of leadership management of a school principal in order to improve the quality of educational performance and education personnel. The principal also has authority for the progress of the school he leads, the principal also has the right to issue regulations to develop his school through discipline coaching by setting a good example such as arriving on time and obeying school rules, Providing motivation for subordinates who perform well. This motivation is in the form of praise and support for teachers to be more enthusiastic in their work. In addition, by giving trust in the form of positions, awarding, by providing bonuses for outstanding teachers, thanks, receiving ideas or opinions, and giving salaries at the beginning of each month.